Effect of charging conditions on the storage performance of a conformable adsorbed natural gas tank packed with HKUST-1 - Baifeng Yang; Jiaying Lu; Yixue Sun (PLoS ONE, 2025)
Adsorbed natural gas (ANG) technology represents a viable option for energy storage solutions. However, the enhancement of the storage performance is constrained by the thermal effect inherent to conformable ANG storage tanks for small dual-fuel ships. This research had developed a COMSOL numerical model for a 200 L conformable ANG storage tank packed with HKUST-1 to simulate the thermal effects resulting from the charging flow rates and temperature, charging modes. Based on the numerical calculation results, the effects of these charging conditions on the storage performance of the conformable storage tank were analyzed and evaluated. The findings suggested that the heat generated throughout the charging process was a crucial factor affecting both the cumulative storage amount and temperature fluctuations within the ANG system. Furthermore, the study revealed that a combination of low charging temperature and cyclic charging significantly mitigated the adverse effect of thermal effects, thereby improving charging efficiency, and enhancing the overall storage performance of the conformable ANG storage tank.